THE ROLE OF BRAND AWARENESS MEDIATES THE RELATIONSHIP CREDIBILITY BETWEEN ENDORSER AND ONLINE PURCHASE INTENTION THROUGH ONLINE SHOPPING SITE BUKALAPAK.COM - AA Sagung Ksanthi Paramhita; Ni Made Purnamie (Journal of Management and Business, 2019)
This study aims to find out how the role of brand awareness mediates the relationship of endorser credibility with online purchase intention by using the online shopping site Bukalapak.com. The location of research was in Denpasar City with the number of respondents 110 people. Data analysis techniques used are Path Analysis. The results showed,  brand awareness has positive and significant effect on purchase intention. Celebrity endorsers has positive and significant effect on brand awareness. Celebrity endorsers has positive and significant effect on purchase intention. Brand awareness able to mediate the influence of celebrity endorser on purchase potential Bukalapak.com.